Cellulose nanowhiskers from coconut husk fibers: Effect of preparation conditions on their thermal and morphological behavior - Rosa, M. F.; Medeiros, E. S.; Malmonge, J. A. [UNESP]; Gregorski, K. S.; Wood, D. F.; Mattoso, L. H. C.; Glenn, G.; Orts, W. J.; Imam, S. H. (Elsevier B.V., 2010)
Cellulose nanowhiskers were prepared by sulfuric acid hydrolysis from coconut husk fibers which had previously been submitted to a delignification process. The effects of preparation conditions on the thermal and morphological behavior of the nanocrystals were investigated. Cellulose nanowhisker suspensions were characterized by Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), thermogravimetric analysis (TGA) and X-ray diffraction. Results showed that it was possible to obtain ultrathin cellulose nanowhiskers with diameters as low as 5 nm and aspect ratio of up to 60. A possible correlation between preparation conditions and particle size was not observed. Higher residual lignin content was found to increase thermal stability indicating that by controlling reaction conditions one can tailor the thermal properties of the nanowhiskers. Published by Elsevier Ltd.
Keywords: Nanowhiskers; Cellulose nanocrystals; Coconut husk fiber; Nanofiber; Thermal behavior; Morphology